Green synthesis of graphene-based metal nanocomposite for electro and photocatalytic activity; recent advancement and future prospective. (January 2023) - Shaheen, Shumila; Saeed, Zohaib; Ahmad, Awais; Pervaiz, Muhammad; Younas, Umer; Mahmood Khan, Rana Rashad; Luque, Rafael; Rajendran, Saravanan
Abstract: The presence of pollutants in waste water is a demanding problem for human health. Investigations have been allocated to study the adsorptive behavior of graphene-based materials to remove pollutants from wastewater. Graphene (GO) due to its hydrophilicity, high surface area, and oxygenated functional groups, is an effective adsorbent for the removal of dyes and heavy metals from water. The disclosure of green synthesis opened the gateway for the economic productive methods. This article reveals the fabrication of graphene-based composite from aloe vera extract using a green method. The proposed mechanism of GO reduction via plant extract has also been mentioned in this work. The mechanism associated with the removal of dyes and heavy metals by graphene-based adsorbents and absorptive capacities of heavy metals has been discussed in detail. The toxicity of heavy metals has also been mentioned here. The Polyaromatic resonating system of GO develops significant π-π interactions with dyes whose base form comprises principally oxygenated functional groups. This review article illustrates a literature survey by classifying graphene-based composite with a global market value from 2010 to 2025 and also depicts a comparative study between green and chemical reduction methods. It presents state of art for the fabrication of GO with novel adsorbents such as metal, polymer, metal oxide and elastomers-based nanocomposites for the removal of pollutants. The current progress in the applications of graphene-based composites in antimicrobial, anticancer, drug delivery, and removal of dyes with photocatalytic efficacy of 73% is explored in this work. It gives a coherent overview of the green synthesis of graphene-based composite, various prospective for the fabrication of graphene, and their biotoxicity. Graphical abstract: Image 1 Highlights: Green synthesis protocol for graphene base nanocomposite. Graphene a wounder material against hazardous materials in wastewater. Removal of heavy metals using green synthesis graphene-based nanomaterials. Degradation of Organic Pollutants using photocatalysis with GO nanomaterial.